CODESRIA Bulletin, Nos 3 & 4, 2019 - Journal System (CODESRIA Bulletin, 2020)
In this issue Editorial Note ————————————1 Note éditoriale ————————————3 Debates and Think Pieces 1. The Dilemma of African Development: Making Policy Choices for Sub-Saharan Africa, Daniel Ngugi ————————— 5 2. Le franc CFA, la France et l’Afrique, Demba Moussa Dembele ——— 9 3. Informal Entrepreneurship: Category of Governance or Practice of Democracy? Robert Nyakuwa —————————— 14 4. What is Development? Vusi Gumede ————————— 20 Tributes 5. Pius Adesanmi: The Man Who Leaves and Lives, Toyin Falola ——– 25 CODESRIA Scientifc Committee Members 2018 - ————————— 29